2018
DOI: 10.12948/issn14531305/22.2.2018.06
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Augmented Reality in Construction and Integration into Smart City

Abstract: This paper presents the current state of AR technology applications in the field of construction through some examples already applied in simulation of the organization of utilities networks, simulation of site organization in various stages, simulation of the new urban plan, modeling of building details, interior organization and navigation site and proposes to design of an IT application that integrates these benefits into a unitary application, easy to use by all parties involved in project: project owner, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The actual cost of implementing AR is frequently addressed in many different publications, but it often leads to different viewpoints about whether it is comparatively expensive or inexpensive. While many studies mention the high cost of AR as a limitation (Hou et al, 2015;Agarwal, 2016;Kodeboyina and Varghese, 2016;Omar and Nehdi, 2016;Piroozfar et al, 2018), other studies find the cost of implementing AR in the construction field as an advantage (Adăscăliţei and Bălţoi, 2018;Chu et al, 2018;Fazel and Izadi, 2018). The diverging opinion on cost of AR is largely intuitive when considering the very broad range of available AR devices, with varying prices in the market.…”
Section: Costmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual cost of implementing AR is frequently addressed in many different publications, but it often leads to different viewpoints about whether it is comparatively expensive or inexpensive. While many studies mention the high cost of AR as a limitation (Hou et al, 2015;Agarwal, 2016;Kodeboyina and Varghese, 2016;Omar and Nehdi, 2016;Piroozfar et al, 2018), other studies find the cost of implementing AR in the construction field as an advantage (Adăscăliţei and Bălţoi, 2018;Chu et al, 2018;Fazel and Izadi, 2018). The diverging opinion on cost of AR is largely intuitive when considering the very broad range of available AR devices, with varying prices in the market.…”
Section: Costmentioning
confidence: 99%
“…Conversely, other researchers stated that developing AR applications is not a major issue, and that stakeholders could develop AR applications and various simulations without substantial time and resources (Adăscăliţei and Bălţoi, 2018). While the time difference of the studies can account for the challenges experienced in the development of content, with older studies reporting challenges in this respect as a consequence of the relatively less mature stage of the technology, more recent studies have also reported development time as being a limitation (Xiang et al, 2019).…”
Section: Development Timementioning
confidence: 99%
“…Based on the potential that AR offers, many large corporations like Google, IBM, Sony and HP are working with many universities to develop it further. Augmented Reality is suitable for applications in almost every subject, especially physics, chemistry, biology, mathematics, history, astronomy, medicine, flight training, project management, and even tourism [31]- [35]. Hence the use of AR can be beneficial in the settings of religious tourism, including pilgrims' visits to Haram.…”
Section: Augmented Reality and Large Buildingsmentioning
confidence: 99%
“…Augmented reality (AR) may be defined as a medium through which pictures can be displayed over a screen. Through this process new virtual elements are created by overlaying and integrating them into the environment (Adascalitei, Baltoi 2018). In contrast, virtual reality (VR) is defined as having the ability to create a simulated environment (Adascalitei, Baltoi 2018).…”
Section: Introductionmentioning
confidence: 99%